OC-017 Autofluorescence-targeted Optical Biopsy Accurately Diagnoses Dysplasia In Barrett's Oesophagus And Can Detect The Field Of Molecular Change. (9th June 2014) - Di Pietro, M; Bird-Lieberman, E; Liu, X; O'Donovan, M; Fitzgerald, R
Abstract : Introduction: Probe-based confocal laser endomicroscopy (pCLE) allows optical biopsies in Barrett's oesophagus (BO) to predict histological outcome but it is subject to sampling error if performed in a random fashion. We used autofluorescence imaging (AFI) to direct pCLE and added molecular biomarkers to the histopathological diagnosis. The aims of this study were to assess the diagnostic accuracy for dysplasia of AFI-targeted optical biopsies and to investigate the correlation between pCLE patterns and field of molecular change. Methods: 46 patients with BO (non-dysplastic BE n = 20, indefinite for dysplasia n = 4, low grade dysplasia n = 10, high grade dysplasia (HGD) or intramucosal cancer (IMC) n = 12) were recruited at a single centre. Patients underwent high-resolution endoscopy followed by AFI and then pCLE was performed on AFI positive (AFI+) areas. Targeted biopsies were taken from AFI+ areas, followed by random biopsies as per Seattle protocol. pCLE sequences were graded according to published criteria. Cyclin A and p53 expression were assessed by immunohistochemistry and aneuploidy by flow-cytometry on AFI-targeted biopsies. Statistical analyses were performed using chi-square test. Results: AFI-targeted pCLE correctly classified all the HGD/EC patients and had a sensitivity and specificity for any grade of dysplasia of 93 and 83%, respectively. The Seattle protocol had similar sensitivity for HGD/IMC and any grade of dysplasia (83 and 89%, respectively). For the per-location analysis, a total of 155 endoscopic areas were analysed with pCLE and molecular biomarkers. pCLE had a sensitivity and a specificity for HGD/IMC and any grade of dysplasia of 100/64% and 78/75%, respectively. Overall, 40% of pCLE irregular sequences corresponded to non-dysplastic areas (false positive). We found a statistically significant enrichment (p < 0.001) of the three molecular biomarkers in pCLE irregular areas (Figure 1 ). After exclusion of dysplastic areas, a significant correlation between pCLE irregularity and biomarker positivity was retained (p = 0.008). The presence of at least 1 positive biomarker significantly correlated with dysplasia both in pCLE irregular (p = 0.01) and pCLE regular areas (p = 0.05). Conclusion: AFI-targeted pCLE has a high diagnostic accuracy for dysplasia in BO. Tissue biomarkers are a useful adjunct to characterise the field of molecular abnormality associated with optical dysplasia. These results suggest that the presence of pCLE irregularity, even in the absence of histological dysplasia, relates to molecular changes and may warrant close follow up. Disclosure of Interest: None Declared.